Stem cells : an alternative therapy for covid-19 and cytokine storm - Verma, Yogesh Kumar (Academic Press, 2024)
Stem Cells: An Alternative Therapy for COVID-19 and Cytokine Storm provides mechanistic insights into the role of stem cells to combat COVID-19 outbreak and other pathologies where cytokines storm is the cause of concern for e.g., radiation exposure, multiple organ failure and sepsis. There has been an increase in number of cases of new diseases in the last decade, including mucormycosis, Zika virus, H1N1 influenza virus, among others. These diseases can be characterized by the induction of cytokine storm, which is mainly responsible for morbidity and mortality. Stem cell therapy has emerged as a potential treatment for viral diseases, including, but not limited to, COVID-19. Interestingly, clinical trials in patients with COVID-19 complications depicted faster recovery in patients post mesenchymal stem cells therapy owing to the decreased cytokines levels, anti-viral effects and regeneration of the infected tissue.